If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 = -5(x + -7) Reorder the terms: 10 = -5(-7 + x) 10 = (-7 * -5 + x * -5) 10 = (35 + -5x) Solving 10 = 35 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 10 + 5x = 35 + -5x + 5x Combine like terms: -5x + 5x = 0 10 + 5x = 35 + 0 10 + 5x = 35 Add '-10' to each side of the equation. 10 + -10 + 5x = 35 + -10 Combine like terms: 10 + -10 = 0 0 + 5x = 35 + -10 5x = 35 + -10 Combine like terms: 35 + -10 = 25 5x = 25 Divide each side by '5'. x = 5 Simplifying x = 5
| -(6+x)8=x+3 | | 8(x+4)=3x+123 | | 3x*(6x-2)+18=-10+2x*(4+9x) | | 3x-(x+8)-2=4x+1 | | 25-3(7a-12)=-(9a-15)+(7-4a) | | y=5(x-5)-25 | | 2x+3xy=-6 | | 100x^2-64y^3= | | 4m-5+2m=13 | | 12=-3z-8-2z | | -(6-3)8=x+3 | | 5/6x-x/3 | | -(6)8=x+3 | | 1/5x-9=3 | | 10x=x+12 | | 26=3x+7(-x-2) | | 7(n-3)=4n+21 | | 3x-18-(6x-4)=10+3*(2+4x) | | 2g-3g+7=-6 | | 7(y+2)=48 | | 0.42=p-0.14 | | 7(y+1)=48 | | 4m-2m+1=-7 | | 15x+100=115 | | .5x+3.5=5 | | 3x-4x+6=12 | | 1/2×b×8=10 | | (3x-7)(4+x)=0 | | 36y=8x-25 | | 4*(-8x+8)=5*(5-5x) | | 7y+14=48 | | 11=5c-6c+3 |